XXVI Brazilian Congress on Biomedical Engineering CBEB 2018, Armação de Buzios, RJ, Brazil, 21-25 October 2018 (Vol. 2) - Costa-Felix, Rodrigo; Machado, João Carlos; Alvarenga, André Victor; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This volume presents the proceedings of the Brazilian Congress on Biomedical Engineering (CBEB 2018). The conference was organised by the Brazilian Society on Biomedical Engineering (SBEB) and held in Armação de Buzios, Rio de Janeiro, Brazil from 21-25 October, 2018. Topics of the proceedings include these 11 tracks: • Bioengineering • Biomaterials, Tissue Engineering and Artificial Organs • Biomechanics and Rehabilitation • Biomedical Devices and Instrumentation • Biomedical Robotics, Assistive Technologies and Health Informatics • Clinical Engineering and Health Technology Assessment • Metrology, Standardization, Testing and Quality in Health • Biomedical Signal and Image Processing • Neural Engineering • Special Topics • Systems and Technologies for Therapy and Diagnosis.
Clinical Engineering and Health Technology Assessment -- Biomaterials, Tissue Engineering and Artificial Organs -- Bioengineering -- Biomedical Devices and Instrumentation -- Biomechanics and Rehabilitation -- Neural Engineering -- Biomedical signal and image processing -- Biomedical Robotics, Assistive Technology and Health Informatics -- Systems and Technologies for Therapy and Diagnosis -- Metrology, Standardization, Testing and Quality in Health -- Special Topics.
Keywords: Biomedical engineering; Medical informatics; Biomaterials; Bioinformatics; Biomedical Engineering and Bioengineering; Health Informatics; Biomaterials; Bioinformatics